2019
DOI: 10.1038/s41467-018-07872-w
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Interplay between hypoxia and androgen controls a metabolic switch conferring resistance to androgen/AR-targeted therapy

Abstract: The original version of this Article contained errors in Fig. 7. In panels e and f, the graph titles incorrectly read 'LNCaP-AdtNs' and 'LAPC4-AdtNs', respectively. These errors have now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Besides APO10, TKTL1 is another biomarker underlying epitope detection in monocytes (EDIM) blood tests. By comparing the sensitivity of the EDIM blood test with conventional tumor biomarkers, studies have shown that this novel test might aid the detection and diagnosis of cholangiocellular carcinoma, PC, and CRC 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides APO10, TKTL1 is another biomarker underlying epitope detection in monocytes (EDIM) blood tests. By comparing the sensitivity of the EDIM blood test with conventional tumor biomarkers, studies have shown that this novel test might aid the detection and diagnosis of cholangiocellular carcinoma, PC, and CRC 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, GPI transcription is suppressed by AR during hypoxia. When GPI was inhibited, therapeutic resistance under hypoxia was reduced, and enzalutamide efficacy was increased 35 . Upregulated glycolysis could improve organ tolerance to hypoxia.…”
Section: Discussionmentioning
confidence: 99%